Impact Of Climate Resilient Technologies In Nandyal District Of Andhra Pradesh - G. Dhanalakshmi,; B. Jamuna Rani,; M. Sudakar,; A. Krishnamoorthy, (Journal of Agricultural Extension Management, 2026)
Climate change refers to a significant and lasting alteration in the statistical distribution of weather patterns over periods ranging from decades to millions of years. In developing countries, crop yield declines are expected in several important crops, with South Asian nations projected to be particularly hard hit. Climate-smart agricultural technologies proved to be the best adaptation strategies followed by farmers for achieving sustainable crop yields. A study on Impact of climate resilient technologies (CRTs) and factors associated in adoption of the technologies was conducted in Nandyal district of Andhra Pradesh. The results of the study indicated that conservation furrows helped in increasing the yield of setaria by 28% (1,418 kg/ha) and castor by 32% (1,332 kg/ha) and in cotton it was 51% higher and in red gram it was 44% higher (1,024 kg/ha). With micro irrigation yield was enhanced by 35% in sweet orange (27 t/ha), tomato 32% (64 t/ha) and in brinjal, it was 41 % higher than control. In the intercropping system of setaria with red gram in 5:1 ratio 28% more yields was recorded. In case of groundnut and red gram intercropping in 7:1 ration the yield recorded was 30% more than the control. Drought tolerant varieties of castor, Bengal gram and groundnut recorded enhanced yield by 25%, (1,330 kg/ha), 23% (1,513 kg/ha) and 50% (1,020 kg/ha) respectively along with additional net returns. Short duration varieties of setaria, groundnut and green gram yielded 32%, 58% and 9% more, respectively, than traditional varieties. Certain characteristics viz., mass media exposure, capacity building programmes attendance, extension contact, perception on climate change and perception on climate resilient technologies had a significant correlation with the adoption of CRTs among the farmersClimate resilient technologies (CRTs),